Synthesis, Characterization and Antitumor Mechanism Investigation of Heterometallic Ru(Ⅱ)-Re(Ⅰ) Complexes - Ma, Xiurong; Lu, Junjian; Yang, Peixin; Huang, Bo; Li, Rongtao; Ye, Ruirong (Frontiers in Chemistry, 2022)
The development of heteronuclear metal complexes as potent anticancer agents has received increasing attention in recent years. In this study, two new heteronuclear Ru(Ⅱ)-Re(Ⅰ) metal complexes, [Ru(bpy)2LRe(CO)3(DIP)](PF6)3 and [Ru(phen)2LRe(CO)3(DIP)](PF6)3 (RuRe-1 and RuRe-2, L = 2-(4-pyridinyl)imidazolio[4,5-f][1,10]phenanthroline, bpy = 2,2'-bipyridine, DIP = 4,7-diphenyl-1,10-phenanthroline, phen = 1,10-phenanthroline), were synthesized and characterized. Cytotoxicity assay shows that RuRe-1 and RuRe-2 exhibit higher anticancer activity than cisplatin, and exist certain selectivity toward human cancer cells over normal cells. The anticancer mechanistic studies reveal that RuRe-1 and RuRe-2 can induce apoptosis through the regulation of cell cycle, depolarization of mitochondrial membrane potential (MMP), elevation of intracellular reactive oxygen species (ROS), and caspase cascade. Moreover, RuRe-1 and RuRe-2 can effectively inhibit cell migration and colony formation. Taken together, heteronuclear Ru(Ⅱ)-Re(Ⅰ) metal complexes possess the prospect of developing new anticancer agents with high efficacy.